Quality of Performance Information for Public Accounability in Estonian Local Governments. Tulemusinformatsiooni kvaliteet Eesti kohalike omavalitsuste tulemusvastutuse raamistikus - Kenk, Karina; Haldma, Toomas (Estonian Discussions on Economic Policy, 2016)
The main purpose of this paper is to assess the comprehensiveness and integrativity of the performance information of local governments in promoting public accountability to its stakeholders using the PDCA cycle model. This study primarily uses document content analysis, reviewing and analysing the information contained in strategic and operational plans, budgets and annual reports of 38 municipalities in Estonia. Results show that the annual budgeting, reporting and decision-making follow a closed-loop cycle, but the integration of strategic planning into the ongoing management process is still not disclosed to the general public, therefore also resulting in limited public accountability and poor governance arrangements